Problem-Driven Political Economy Analysis : The World Bank's Experience - Fritz, Verena (Washington, DC: World Bank, 2013)
Problem-driven political economy analysis holds considerable promise to help development practitioners identify what policies and strategies are most likely to succeed in addressing difficult and persistent development challenges. This volume is the result of a systematic effort to take stock of what the World Bank has learned from efforts to mainstream this approach. The eight cases presented here are good practice examples that illustrate and reflect on what the Bank has been able to achieve in this area so far.